Efektivitas Pengawasan Majelis Pengawas Daerah dalam Mengurangi Pelanggaran Notaris Terhadap Pelaksanaan Jabatannya - Triana Handayani; Felicitas Sri Marniati; Andrea Septiyani (Postgraduate of Jayabaya University, 2019)
The purpose of the establishment of the Supervisory Board is to provide guidance and supervision to the Notary. Indication that showed Supervision is actualy on target or effective would be no more any violation committed by the Notary in carrying out his duties.From the examinations resulf carried out by the MPD of South Jakarta out of the empirical data showeds that there are still violations committed by Notaries in which such violation has the West Java High Court. The research method used is a normative juridicial method. The data source used is secondary data sources supported by primary data sources in the form of court decisions and interviews with Notaries, MPD and MPW. The analysis technique used here in descriptive analisys method. The results showed there’s some Notary who has commitetted violation of Article 16 paragraph (1) letter a of Act Number 2 Year 2014 concerning Amendments to UUJN, by careful enough in creating the Deed resulted in the giving out of written summon. In the case verdict of the West Java High Court Number: 87 / PDT / 2018 / PT.BDG dated March 27 2018, the Notary considered to have commits an unlawful act, so that the Deed is requested to be null and void by the aggrieved party, and the Panel of Judges ruled that the Deed is null and void. The violation by the Notary indicates that MPD supervision has not been effective. The effectiveness of supervision is influenced by legal factors, law enforcement, facilities, society, and culture. Empirical data shows that the society factors which become hurdle to the effectiveness of the Notary’s supervision, are inadequate understanding of the parties / parties to the UUJN and the prevailing regulations which contribute to the violations of the implementation of the Notary’s duties